Performance and carbon turnover in fast- and slow-growing broilers submitted to cyclic heat stress and fed on high-protein diets - Campos, D. M. B.; Macari, M.; Fernadez-Alarcon, M. F.; Nogueira, W. C. L.; Souza, F. A. de; Hada, F. H.; Lunedo, R.; Denadai, J. C. [UNESP] (Taylor & Francis Ltd, 2016)
Two experiments were conducted to test the hypothesis that when using similar protein/amino acid diets and environment temperature conditions, the performance and carbon turnover in muscle and liver tissues, as measured by the incorporation of stable isotopes (C-13/C-12), must be different between fast-growing Cobb 500 (R) and slow-growing Label Rouge broilers.For both experiments (Cobb and Label Rouge), 21-d-old birds were distributed in a completely randomised, 3x3 factorial design; three environmental temperatures (cyclic heat stress ad libitum, 22 degrees C ad libitum, and 22 degrees C restricted) and three crude protein concentrations (189.1, 210 and 220g/kg CP) were used.The Cobb 500 (R) had better performance with higher concentrations of crude protein. Cyclic heat stress (a temperature factor), negatively affected this genetic strain's performance. For the Label Rouge birds, the crude protein concentrations in the diet presented inconsistent results and cyclic heat stress did not affect the performance.The carbon turnover rate was affected in the Cobb 500 (R) strain, with a high protein content reducing carbon turnover in the evaluated tissues (liver and muscles). Feed intake had a greater impact on carbon turnover rates than cyclic heat stress. The Label Rouge birds were not affected by the evaluated factors, suggesting that genetic improvement has a leading role on tissue carbon turnover.There is a genetic influence on carbon turnover in the liver and muscle tissues of broiler chickens. In addition, genetically fast-growing broilers are more susceptible to variations in diet composition and environmental temperature than less rapidly growing animals.